Noun Representation in AAC Grid Displays: Visual Attention Patterns of People with Traumatic Brain Injury. (March 2015) - Brown, Jessica; Thiessen, Amber; Beukelman, David; Hux, Karen
Abstract Clinicians supporting the communication of people with traumatic brain injury (TBI) must determine an efficient message representation method for augmentative and alternative communication (AAC) systems. Due to the frequency with which visual deficits occur following brain injury, some adults with TBI may have difficulty locating items on AAC displays. The purpose of this study was to identify aspects of graphic supports that increase efficiency of target-specific visual searches. Nine adults with severe TBI and nine individuals without neurological conditions located targets on static grids displaying one of three message representation methods. Data collected through eye tracking technology revealed significantly more efficient target location for icon-only grids than for text-only or icon-plus-text grids for both participant groups; no significant differences emerged between participant groups.